Use of chicken manure extract for biostimulation and enhancement of perchlorate rhizodegradation in soil and water media - Mwegoha, William J. S.; Mbuya, Odemari S.; Jai, Amita; Ugochukwu, Ngozi H.; Abazinge, Michael D. (Taylor & Francis Online, 2024)
A research paper submitted to Bioremediation Journal Volume 11, 2007 - Issue 2, Pages 61-70